Analisis en la implementacion de medidas de seguridad en las construcciones residenciales de dos niveles - Vásquez Lovos, Bryan Francisco VL12001; Espinoza Reyes, Carolina María ER19014; Chavéz García, Yeniffer Maricela CG17073 (2025)
Resumen